CORAL REEF ECOSYSTEM VULNERABILITY INDEX TO OIL SPILL: CASE OF PRAMUKA ISLAND AND BELANDA ISLAND IN SERIBU ISLANDS - Noveldesra Suhery; Ario Damar; Hefni Effendi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
Vulnerability analysis is one of the methods for determining effective management of coastal and marine resources. Seribu islands potentially affected due to oil spills. The oil spills incident in this area caused by shipwreck from traffic on Tanjung Priok port and ALKI 1, as well as accident of petroleum exploration and exploitation. At least, oil spills in Seribu Islands have been recorded since 2003, 2004, 2006, 2007 and 2008. This study aims to calculate the vulnerability index of Pramuka island and Belanda island in the Seribu Islands. This research was conducted by using a theoretical approach of vulnerability (V), which is a function of exposure (E), sensitivity (S) and adaptive capacity (AC). The parameters in exposure category are tidal type, tidal range, wave height, substrat type, and water depth. Parameters in sensitivity category are growth type of reef, slope, protected ecosystem, coverage percentage, coral density, protected species, and fish abundance. Parameters in adaptive capacity are oil spill contingency system, conservation institution, community response, and economic dependence. Data of each parameter were transformed into a score ranging from 1 to 5. The formula of vulnerability index using addition and subtraction model where; V = E + S – AC. The results indicate that Seribu Islands have vulnerability status from moderate to high, which 4.15 for Pramuka island and 6.39 for Belanda island. Keywords: vulnerability index, Seribu islands, coral reef, oil spill